Sebuah English: English - Chandra, Agus Firdaus; Nasution, Syamruddin; Adynata; Raba'in, Jamaluddin; Arni, Jani (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
This article analyzes munākahāt hadiths in Fath al-Mun’im by Mūsā Shāhīn Lāshīn and his contribution to the reform of Islamic family law. While these hadiths are central in shaping legal thought, the interpretation has often remained literalist, producing a gap between normative texts and present socio-legal realities such as child marriage, women’s consent, and dowry inflation. Addressing this gap is crucial for developing a hadith-based framework that is responsive to contemporary challenges in Muslim family life. The study aims to examine how Lāshīn constructs legal reasoning on munākahāt and to evaluate the implications of his method for family law reform. Using a qualitative, library-based approach, it applies content analysis to the ten-volume Fath al-Mun’im, supported by classical fiqh and modern scholarship. Analytical lenses include maqasid al-shari’ah and the sociology of knowledge. The findings show that Lāshīn develops an integrative framework that harmonizes hadith authority with ethical priorities and social realities. He affirms women’s agency, critiques burdensome dowries, and classifies marriage rulings according to context. His approach, rooted in fiqh al-awlawiyyāt and comparative madhhab analysis, offers not only a moderate and contextual model of hadith-based ijtihād but also practical guidance for policymakers in shaping equitable and sustainable Islamic family law.